(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The study was aimed at evaluating the physicochemical properties of phosphorylated tiger nut starch (TNP) and its disintegrant properties in immediate release ibuprofen tablets. Native tiger nut starch (TNS) was modified by phosphorylation with disodium hydrogen orthophosphate at 130oC and its physicochemical properties were evaluated. Ibuprofen tablets were formulated with TNP and sodium starch glycolate (SSG) at concentrations of 5.0, 7.5, 10.0 and 15.0% as disintegrants. Phosphorylation of TNS led to improved flow properties and swelling and hydration capacities among other changes in the physicochemical properties. TNP had comparable properties with SSG. FTIR study confirmed modification and also showed that TNP is compatible with ibuprofen powder. Ibuprofen tablets produced with TNP as disintegrant had acceptable tablet properties comparable to those produced with SSG. The disintegrant potential improved with increased concentration of TNP. The results indicate that TNP has a promising disintegrant potential in tablet formulations. Dhaka Univ. J. Pharm. Sci. 18(1): 21-29, 2019 (June)